Peningkatan Partisipasi Belajar IPS Melalui Strategi Pembelajaran Everyone Is A Teacher Here Pada Siswa Kelas V SD Negeri 01 Plesungan Tahun 2015/2016 - KUSUMA DEWI, TRI ASTUTI (2016)
Tri Astuti Kusuma Dewi / A510120088. Increased Participation IPS Learning Through Learning Strategies Everyone Here Is A Teacher In Class V students of SD Negeri 01 Plesungan Year 2015/2016. Essay. The Faculty of Education, University of Muhammadiyah Surakarta. February, 2016. The purpose of this research is to increase the participation of social studies through learning strategies Everyone is a teacher here in the fifth grade students of SD Negeri 01 Plesungan Year 2015/2016. The subjects of this study were students and teachers of the class V SD Negeri 01 Plesungan. Based on the results of a classroom action research conducted, the results of the study can be summarized as follows: The participation of students in the learning process of each cycle is performed has increased. In the aspect of cooperation and involvement of students in the current group Pre Cycle of 41.17%, in the first cycle was 55.88%, in Cycle II amounted to 73.52%. In the aspect of the task assigned by the teacher when the Pre Cycle of 38.23%, in the first cycle was 58.82%, in Cycle II amounted to 82.35%. In the aspect of the courage to ask questions during the Pre Cycle of 38.23%, in the first cycle was 52.94%, in Cycle II amounted to 79.41%. In the aspect of boldly answered questions during the Pre Cycle of 44.11%, in the first cycle was 61.76%, in the second cycle of 85.29%. While student learning outcomes in social studies from each cycle were carried increased in accordance with the KKM (≥65). In Pre Cycle of 38.23%, on the first cycle was 55.88%, in Cycle II amounted to 73.52%.